Inequality in dental expenditures among Iranian households: A cross-sectional survey using the National Health Accounts - Arash Rashidian; Parisa Mehdizadeh; Nooredin Dopeykar; Mostafa Hosseini; Alireza Olyaeemanesh (Wolters Kluwer Medknow Publications, 2020)
Background: Recently, inequality in dental care has become increasingly popular in both developed and developing countries as a matter of health policy. Thus, the aims of this study were examining inequality in dental care expenditures and assessing the effects of insurance coverage and other variables on these services. Materials and Methods: In this cross-sectional and descriptive-analytical study, we used secondary data of the National Health Accounts that has been conducted in 2008 in Iran. The sample size was 17,239 households in all over the country. All analyses were performed by Stata software using Mann-Whitney test and logistic regression. P < 0.05 was considered statistically significant. To determine inequality in dental services, the concentration index (CI) was used. Results: CI for total dental expenditures was 0.315 and for orthodontics was 0.6. Findings showed that out-of-pocket expenditure for dental care was progressive and there was a significant relationship between total dental expenditure with residence areas (odds ratio [OR] =1.3; P > 0.001), complementary insurance coverage (OR = 1.3; P > 0.001), family size (OR = 1.46; P > 0.001), and income (OR = 1.3; P > 0.001). Conclusion: Dental expenditures were progressive in Iran, and the rich have paid more share for these services. It seems that implementing insurance programs, changes in the financing of dental care, development of insurance basic benefits package, supporting programs for the poor, adopting educational policies, and promoting oral health for vulnerable people can have an effective role in decreasing inequality in using dental services.